(untitled) (Research, Society and Development, 2026)
Stroke is a leading cause of global mortality and disability. This study aims to analyze the impact of early palliative care implementation on quality of life and decision-making for patients with acute stroke. The methodology employed was an integrative literature review, with searches conducted in PubMed and VHL (LILACS) databases, resulting in a selection of 22 articles published between 2006 and 2025. Results demonstrate that while palliative care significantly improves symptom management, such as pain and dyspnea (increasing opioid use by up to 31 times when necessary), and reduces family anxiety, its implementation remains delayed and underutilized. Cultural barriers and failures in prognostic communication lead to futile interventions and untreated suffering. The study concludes that early integration of a palliative approach, alongside curative treatment, is essential to align medical procedures with patient values, optimizing comfort and family satisfaction without accelerating death.